Nasal Carriage of Multi Drug Resistant Staphylococcus aureus Among School Going Children of Kathmandu Valley - Gautam, Babita; Gautam, Anjana; Khadka, Rama (Tribhuvan University Journal of Microbiology, 2022)
Objectives: The present study was conducted to determine the multi drug resistant Staphylococcus aureus from nasal carriage among the school children of Kathmandu, Nepal. Methods: This study was carried out from February to May 2018. A total of 100 nasal samples were collected from school going children of 7-15 years old. Nasal swabs collected were subjected to standard bacteriological techniques to identify S. aureus isolates. Antimicrobial susceptibility test was performed on Muller-Hinton Agar (MHA) by modified Kirby-Bauer disc diffusion method. Results: Among 100 samples, 18% significant growth of S. aureus was found in which female had higher prevalence rate (18.03%) than male (17.95%). Prevalence was also high among age group 11-14 (19.44%), in private school (61.11%) compared to government school. Unhygienic practices like nose picking habit (77.78%), not covering nose while sneezing (55.56%), not using separate towel in family (88.89) were common. None of the isolates were MRSA and all showed resistance to amoxicillin and sensitive to chloramphenicol. Among 18 isolates 13 were MDR and they showed relatively high resistance to co-trimoxazole (44.44%) followed by ciprofloxacin (38.89%) and erythromycin (27.78%). Conclusion: This study showed a high prevalence of MDR S. aureus carriage in school children indicating the spread of MDR S. aureus in the community.